Breeding fat cats: Affirmative action, Black Economic Empowerment, and Namibia's post-colonial elite formation - Henning Melber (Danish Institute for International Studies (DIIS), 2006)
The Independence of Namibia came about in 1990 as the result of a negotiated decolonisation process. The controlled change implied a perpetuation of the existing socio-economic inequalities under the former liberation movement as the new government. The country's constitution endorsed the status quo in terms of property rights. Ever since then Namibia has remained the country with the highest income discrepancies in the world. In the absence of any coherent socio-economic redistributive measures for the formerly colonised majority, strategies such as affirmative action and Black Economic Empowerment have claimed to uplift the previously disadvantaged groups. The paper shows, that this has so far resulted merely in a slight diversification of the local class structure, with the new political office bearers and its clientele as the beneficiaries. They secure material privileges and individual gains by means of access to the state apparatus and control over resources, while the majority of the people remain poor. Consequently, Namibia's BEE so far translates merely into a classbased interest policy to legitimise the (self-)enrichment of a new small black elite.
Keywords: 330; Ethnische Diskriminierung; Rassenpolitik; Wirtschaftspolitik; Entwicklung; Armut; Wirtschaftslage; Namibia